1998
DOI: 10.2307/3284641
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cryptosporidium Oocysts and Giardia Cysts in the Tissues of Eastern Oysters (Crassostrea virginica) Carrying Principal Oyster Infectious Diseases

Abstract: The potential cross-reactivity of the combined Cryptosporidium/Giardia direct immunofluorescence antibodies (IFA) of MERIFLUOR and HYDROFLUOR-COMBO tests was examined against tissues containing known developmental stages of 12 pathogens causing the principal infectious diseases in oysters. Spores of Haplosporidium nelsoni and Haplosporidium costale produced positive acid-fast stain (AFS) reactions similar in intensity to Cryptosporidium parvum oocysts. Hexamia nelsoni trophozoites produced positive IFA reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…In another study, infective C. parvum oocysts were detected in mussels and cockle from a shellfish-producing region that account for the majority of European shellfish production (Gomez-Bautista et al, 2000). All these data suggested that mussels and cockles could act as a reservoir of C. parvum infections to humans (GomezBautista et al, 2000;Graczyk et al, 1998;Graczyk et al, 2001;Lowery et al, 2001). In the present work, the green mussels (Perna viridis) native to the mouth of the Chao Phraya River have been examined for the presence of Cryptosporidium oocysts.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In another study, infective C. parvum oocysts were detected in mussels and cockle from a shellfish-producing region that account for the majority of European shellfish production (Gomez-Bautista et al, 2000). All these data suggested that mussels and cockles could act as a reservoir of C. parvum infections to humans (GomezBautista et al, 2000;Graczyk et al, 1998;Graczyk et al, 2001;Lowery et al, 2001). In the present work, the green mussels (Perna viridis) native to the mouth of the Chao Phraya River have been examined for the presence of Cryptosporidium oocysts.…”
Section: Resultsmentioning
confidence: 97%
“…Samples were placed on glass microscope slides, air dried and stained with a specific monoclonal antibody against an epitope of Cryptosporidium oocyst wall, and fluorescein isothiocyanate (FITC) labelling as described by the manufacturer Monofluo ® Kit Cryptosporidium (Sanofi Diagnostics Pasteur, France). The oocysts were identified under an FITC filter using fluorescence microscopy (OLYMPUS, Model BX 51), according to the criteria proposed by Graczyk et al (1998), i.e. brilliant green fluorescence, correct shape and size of the FITC-labelled objects with clearly visible oocyst wall.…”
Section: Detection Of Cryptosporidium Oocystsmentioning
confidence: 99%
“…After DAPI/PI staining, samples were incubated with 5 μl of monoclonal antibodies labeled with fluorescein isothiocyanate (FITC) (Aqua-Glo G/C, Waterborne, New Orleans, LA). Individual oocysts were firstly identified by microscopy under a FITC filter according to the criteria proposed by Graczyk et al (1998) (i.e., brilliant green fluorescence, correct shape and size of the FITC-labeled objects, and clearly visible oocyst wall) before being examined for DAPI and PI inclusion/ exclusion under the appropriate filters. Photomicrographs were taken with an Olympus DP70 digital camera.…”
Section: Determination Of Oocyst Viabilitymentioning
confidence: 99%
“…or of other acid-fast stain-positive pathogens (e.g., Haplosporidium spp.) (20,26). The other staining methods (e.g., dimethyl sulfoxide-carbol fuchsin or safranin-methylene blue) are laborious and have low sensitivity and specificity (18).…”
mentioning
confidence: 99%
“…may be successfully performed by immunofluorescence assays, but this technique is often limited by the occurrence of cross-reactions with other microorganisms, the lack of monoclonal antibodies for all Cryptosporidium species, or its low sensitivity and high cost (3,16,18,19,24,26). Furthermore, when antibody-based methods are used for shellfish samples, some identification problems arise due to the fact In this study, evidence of the presence of C. parvum in clams collected at the mouths of the Vomano and Vibrata Rivers led us to hypothesize that ruminants grazing near the rivers might be sources of contamination.…”
mentioning
confidence: 99%